The constellation of the Llama in the Peruvian Andes - Zuidema, R. T. (1976)
The most systematic description of the constellations known by the ancient Peruvians is found in chapter 29 of the Quechua Treatise on the religion and mythology of the town of San Damián de Checa, province of Huarochirí, edited by Father Francisco de Ávila at the end of the 16th century. .